Cancer-Associated Venous Thromboembolism Treatment With Anti-Xa Versus Weight-Based Enoxaparin: A Retrospective Evaluation of Safety and Efficacy. Issue 9 (September 2021) - Hart, Kayla; Andrick, Benjamin; Grassi, Stacey; Manikowski, Jesse; Graham, Jove
Background: Venous thromboembolism (VTE) is a complication of cancer, for which low-molecular-weight heparin (LMWH) remains the preferred anticoagulant. Enoxaparin is traditionally dosed using weight. In certain populations, monitoring anti-Xa levels for therapeutic effect provides pharmacokinetic guidance for dose adjustments. There is a paucity of data regarding anti-Xa–directed enoxaparin dosing for treatment of VTE in patients with cancer. Objective: This study aims to evaluate efficacy (recurrent VTE) and safety (major bleed) between enoxaparin anti-Xa–guided dose adjustments and weight-based dosing in patients with cancer-associated VTE. Methods: This single-center, retrospective cohort study examined patients treated with enoxaparin for cancer-associated VTE using data from electronic health records. Results: There were 674 patients who met the inclusion criteria, with 283 receiving anti-Xa–directed dose adjustments. Recurrent VTE, major bleed, or all-cause death occurred in 102 of 283 patients (36%) in the anti-Xa cohort and 166 of 391 patients (42.5%) in the weight-based cohort (hazard ratio [HR] = 0.73; 95% CI = 0.57-0.93; P = 0.01). When death was removed from the composite end point, there was no significant difference between the cohorts in recurrent VTE or major bleed (HR = 1.18; P = 0.38). In the anti-Xa cohort, a total of 1584 anti-Xa peak levels were collected, with 1324 (83.6%) drawn correctly in relation to enoxaparin administration. Of those, 714 (53.9%) were within therapeutic range. Conclusion and Relevance: Patients with cancer receiving anti-Xa–guided enoxaparin dose adjustments for initial VTE, compared with weight-based dosing, had no significant difference in the rate of recurrent VTE or major bleed.